The Practice Effect on Time-Based Prospective Memory: The Influences of Ongoing Task Difficulty and Delay - Guo, Yunfei; Liu, Peiduo; Huang, Xiting (Frontiers in Psychology, 2019)
The practice effect on prospective memory refers to the phenomenon that prospective memory performance can improve with behaviour training. Some studies have found that event-based prospective memory (EBPM) can benefit from practice. However, few studies have focused on the practice effect on time-based prospective memory (TBPM). In the present study, we planned to explore whether the practice effect on TBPM existed consistently and what its processing mechanism was. In Experiment 1, we tested whether the practice effect existed at all under different background task conditions. The results showed that the practice effect existed only under an easy ongoing task condition. When a 600 ms delay was added after each difficult ongoing task in Experiment 2, we found the same effect as for the easy ongoing task condition in Experiment 1. In addition, the results also suggested that the practice effect was closely related to the improvement in the effectiveness of time monitoring.